Feasibility of Implementing a Trains Ticket Management System in Iraq Based on Global Experience - Hiba Abdalsalam Saeed (International Journal of Computers and Informatics, 2026)
This study explores the feasibility of adopting a modern digital system for managing train tickets in Iraq, drawing on the experiences and best practices of leading countries in this field, such as the United States, Russia, and Turkey. The study employs a comparative analytical approach, supported by a conceptual system design. Through comparative analysis, it examines the gap between the current state of train management services in Iraq and more advanced international systems. The findings indicate several weaknesses, particularly in the digital ticketing infrastructure, data processing, and the system’s level of digital integration. To address these issues, the study proposes a phased implementation plan, starting with simple digital services and evolving over time into a more integrated smart transportation system. Results also suggest that leveraging successful international practices, especially in areas such as e-ticketing, digital payment methods, and data utilization in operations, can improve efficiency and enhance passenger satisfaction. These improvements contribute to streamlining procedures, facilitating access to services, and supporting future integration with broader smart transportation solutions. Study concluded that Iraq has a real opportunity to develop a modern and efficient train ticketing system by leveraging international expertise that has achieved passenger satisfaction and significant economic gains, provided that this development is supported by sound infrastructure built according to international standards and principles, and by the gradual adoption of technology in line with international standards.